Overview of Fatty Acid Synthesis and its Role in Obesity-Related Diseases - Li, YongChang (The Meducator, 2016)
Obesity is a medical condition attributed to abnormalities in fatty acid metabolism. According to the World Health Organization, more than 1.4 billion adults are overweight, and 500 million of these adults are categorized as obese. The World Health Organization has categorized this significant onset of obesity as an epidemic. The lipid synthesis process and its role in obesity-related diseases has been investigated extensively. In this article, we summarized the mechanism of fatty acid synthesis and its dysfunction in type 2 diabetes. We also investigated the effects of commercial and novel drugs, and exercise on fatty acid synthesis as methods to mediate weight loss.